Synergy among Exocyst and SNARE Interactions Identifies a Functional Hierarchy in Secretion during Vegetative Growth. Issue 9 (22nd July 2020) - Larson, Emily R.; Ortmannová, Jitka; Donald, Naomi A.; Alvim, Jonas; Blatt, Michael R.; Žárský, Viktor
Abstract : Direct interactions between exocyst and SNARE subunits hierarchically coordinate secretion at the plasma membrane for plant growth. Abstract: Vesicle exocytosis underpins signaling and development in plants and is vital for cell expansion. Vesicle tethering and fusion are thought to occur sequentially, with tethering mediated by the exocyst and fusion driven by assembly of soluble NSF attachment protein receptor (SNARE) proteins from the vesicle membrane (R-SNAREs or vesicle-associated membrane proteins [VAMPs]) and the target membrane (Q-SNAREs). Interactions between exocyst and SNARE protein complexes are known, but their functional consequences remain largely unexplored. We now identify a hierarchy of interactions leading to secretion in Arabidopsis ( Arabidopsis thaliana ). Mating-based split-ubiquitin screens and in vivo Förster resonance energy transfer analyses showed that exocyst EXO70 subunits bind preferentially to cognate plasma membrane SNAREs, notably SYP121 and VAMP721. The exo70A1 mutant affected SNARE distribution and suppressed vesicle traffic similarly to the dominant-negative truncated protein SYP121 ΔC, which blocks secretion at the plasma membrane. These phenotypes are consistent with the epistasis of exo70A1 in the exo70A1 syp121 double mutant, which shows decreased growth similar to exo70A1 single mutants. However, the exo70A1 vamp721 mutant showed a strong, synergy, suppressing growth and cell expansion beyond the phenotypic sum of the two single mutants. These data are best explained by a hierarchy of SNARE recruitment to the exocyst at the plasma membrane, dominated by the R-SNARE and plausibly with the VAMP721 longin domain as a nexus for binding.